2-(3,4-Dichlorophenyl)-N-(1,3-thiazol-2-yl)acetamide - Nayak, Prakash S. (International Union of Crystallography, 2013)
In the title compound, C(11)H(8)Cl(2)N(2)OS, the mean plane of the dichlorophenyl ring is twisted by 61.8 (1)° from that of the thiazole ring. In the crystal, molecules are linked via pairs of N—H⋯N hydrogen bonds with an R (2) (2)(8) graph-set motif, forming inversion dimers which stack along the a-axis direction.